Response of Soil, Growth, and Biomass Properties of Lupin (Lupinus albus L.) to Wood ash and Sawdust - Shakir Bahaddin Shakir (Zanco Journal of Pure and Applied Sciences, 2024)
Two organic carbon resources (wood ash and sawdust) were applied in the study site to assess their profound effects on soil properties and growth and biomass properties of lupin (Lupinus albus L.). Because of their contribution to improving soil structure, enhanced water-holding capacity, and increased carbon sequestration. The experiments were conducted in mid-November 2022 at Grdarasha Research Station, College of Agricultural Engineering Sciences, Salahaddin University-Erbil, Iraq. The experiment includes two organic amendments (wood ash and sawdust) as a treatment and Control. Results showed that the application of wood ash and sawdust improved and raised the number of essential elements and heavy metals in the soil, which in turn boosted the ability of the roots to absorb nutrients. The highest germination percentage, plant height, and leaf number were observed in the ash treatment (95.00 %, 22.00 cm, and 21.22) respectively. The great values of fresh and dry shoot weight were found in sawdust treatment 63.78 and 14 g/plant) respectively. The effects of treatments were not significant on root length and fresh and dry root weights. The final findings showed that adding various forms of organic carbon could alter the chemical characteristics of the soil. This, in turn, might have a good impact on microbes, which can subsequently help plants grow by converting, solubilizing, and mobilizing soil nutrients. Furthermore, lupin plants appeared to be a form of phytoremediation, or absorption, for certain heavy metals.